Replacement Effect of Fish Meal by Plant Protein Sources in Olive Flounder (Paralichthys olivaceus) Feeds with an Addition of Jack Mackerel Meal on Growth, Feed Availability, and Biochemical Composition - Seong Il Baek; Hae Seung Jeong; Sung Hwoan Cho (Aquaculture Nutrition)
Application of feed stimulants is very helpful to increase the feed intake of fish, especially in the development of low fish meal (FM) diets. FM replacement effect by various plant protein sources (corn gluten meal (CGM), soy protein concentrate (SPC), and corn protein concentrate (CPC)) in diets with an addition of jack mackerel meal (JMM) as feed stimulants on growth, feed availability, and biochemical composition of olive flounder was elucidated. An experimental design of two-way (two replacement levels (25% and 50%) × 3 replacement sources (CGM, SPC, and CPC)) analysis of variance was adopted. Seven diets were formulated. Amount of 60% FM was contained in the control (Con) diet. In the Con diet, 25% and 50% FM were replaced by CGM, SPC, and CPC with an addition of 12% JMM as feed stimulants, referred to as the CGM25, CGM50, SPC25, SPC50, CPC25, and CPC50 diets, respectively. Four hundred and twenty juvenile fish were distributed into 21 flow-through tanks. All diets were assigned to triplicate groups of fish. Fish were hand-fed to satiation twice a day for 56 days. Both dietary replacement levels and sources had statistical effect on weight gain (P<0.0001 and P<0.045, respectively), specific growth rate (SGR) (P<0.0001 and P<0.033), and feed consumption (P<0.0001 and P<0.03) of fish. Dietary increased FM replacement levels lowered weight gain, SGR, and feed consumption of fish. Weight gain, SGR, and feed consumption of fish fed the Con and CGM25 diets were statistically (P<0.05) greater than those of fish fed the CGM50, SPC50, and CPC50 diets. Both replacement level and source had no statistical effect on feed utilization, biochemical composition except for statistical effect of replacement source on glycine content of fish, and lysozyme and superoxide dismutase (SOD) activities of fish. FM up to 25% could be substituted with CGM, SPC, and CPC in the olive flounder feeds supplemented with 12% JMM as feed stimulants without compromising growth, feed utilization, and lysozyme and SOD activities.